Upaya Edukasi Kader Kesehatan dan Ibu Hamil untuk Peningkatan Cakupan Imunisasi Dasar Lengkap di Kecamatan Pamotan Kabupaten Rembang - Nurhasmadiar Nandini (Indonesian Journal Publisher, 2021)
Immunisation is one of the health programs which considered cost-effective and able to prevent millions of deaths and disability which caused by diseases which could be prevented by immunisation. For the past years, the coverage of Basic Complete Immunisation has been increasing in several areas in Central Java. However, there were still some community groups that believed immunisation was harmful for their children and they did not allow their children to be vaccinated. This condition could cause a new case of diseases which usually can be prevented by immunisation, such as Polio, Diphtheria, Tetanus, Hepatitis, and many more. Therefore, this program held to refresh the cadres knowledge about immunisation also provide more knowledge for pregnant mother about immunisation so they agree to let their children vaccinated after they born until they complete the basic immunisation. This community service heldin January – February 2020 in Sendangagung Village, Pamotan, Rembang District. The participants were health cadres and pregnant woman in Sendangagung Village, Pamotan, Rembang District. This event started with a mini pre-test, explanation about immunisation, and discussion. Participants stated that this event increase and refresh their knowledge about immunisation. Moreover, participants also get a booklet about the immunisation so the health cadres might use this booklet as their education media to educate other pregnant women and toddler’s parents about immunisation.